TISSUE CULTURE STUDY OF ANY PULSE CROP FOR CALLUS INDUCTION - ANUPAM KUMARI (International Journal of Multidisciplinary Research and Studies, 2020)
In the majority of crop breeding efforts, the rate of yield increment is inadequate to meet the rising demand for food that is being driven by the fast-increasing population throughout the world. The extremely lengthy lifetime of the crop poses a barrier in the way of enhanced crop variety creation in plant breeding due to the fact that there is not enough time. It is possible that developing a new cultivar will take between one and twenty years due to the several processes of crossing, selecting, and testing that are required in the development of new plant types. Rapidly developing superior plant varieties is one strategy that might help alleviate the challenges associated with a lack of food and increase the level of food security. The traditional agricultural practises that have been used for a considerable amount of time have led to a reduction in the genetic variety of crops. Several conventional and molecular methods have been utilized, such as genetic selection, mutagenic breeding, somaclonal variations, whole-genome sequence-based approaches, physical maps, and functional genomic tools, in order to improve agronomic traits associated with yield, quality, and resistance to biotic and abiotic stresses in crop plants. These methods include genetic selection, mutagenic breeding, and somaclonal variations.